THE EFFECT OF WORK ENVIRONMENT AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE WITH WORK CULTURE AS AN INTERVENING VARIABLE - Nur, Nur Khairiyah Anita Nasution; Zunaidah; Isni Andriana (I-Finance Journal, 2024)
This study aims to determine, analyze and apply the influence of the work environment and organizational commitment on employee performance with work culture as an intervening variable on employees of PT Bank Tabungan Negara Palembang Branch Office. The population in this study were all employees of PT Bank Tabungan Negara Palembang Branch Office, namely 105 people. Then the sample was taken based on saturated sampling where all members of the population of 105 people were all used as samples. The analysis technique uses the Partial Least Square method using SmartPLS software with hypothesis testing based on the p value <0.05 or t count> 1.96 then the exogenous variable affects the endogenous variable and vice versa. The results showed that the work environment variable had no effect on performance, Organizational commitment variables have no effect on performance, Work culture variables affect performance, The work environment variable affects work culture, Organizational commitment variables affect work culture, Work environment variable affects performance with work culture variable as intervening variable, Organizational commitment variable affects performance with work culture variable as intervening variable.  The conclusion shows that only work culture variables affect performance, while work environment variables and organizational commitment have no effect on audit quality. Work environment variables and organizational commitment affect work culture. Work environment variables and organizational commitment affect performance with work culture variables as intervening variables.